2004
DOI: 10.1111/j.1399-3054.2004.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone symptoms in leaves of woody plants in open‐top chambers: ultrastructural and physiological characteristics

Abstract: This study was carried out in the summer of 2001 at the Lattecaldo open‐top chamber research facility (Canton Ticino, southern Switzerland). The aim of this research study was to examine the behaviour of Fraxinus excelsior, Prunus avium and Viburnum lantana seedlings grown in charcoal‐filtered (CF) (∼ 50% of the ambient O3) and non‐filtered (NF) (∼ 92% of the ambient O3) air open‐top chambers. Investigations included the assessment of visible foliar symptom development, anatomical and ultrastructural analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 59 publications
(77 reference statements)
5
51
1
2
Order By: Relevance
“…Besides the direct action of the antioxidant, anthocyanins protect the chloroplasts from excess excitation by activating a controlled energy dissipation process and, hence, the potential for oxidative damage (Gravano et al 2004). Comparative values of stomata density between plants of Psidium guajava 'Paluma' exposed to the environment and those kept inside the greenhouse with fi ltered air.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the direct action of the antioxidant, anthocyanins protect the chloroplasts from excess excitation by activating a controlled energy dissipation process and, hence, the potential for oxidative damage (Gravano et al 2004). Comparative values of stomata density between plants of Psidium guajava 'Paluma' exposed to the environment and those kept inside the greenhouse with fi ltered air.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of O 3 at ambient concentrations through the stomata and the related accumulation of reactive oxygen species within plant leaves can cause the collapse of parenchym cells leading to decreased rates of photosynthesis and plant growth (Kärenlampi and Skärby 1996). Ozone-induced injuries present a wide range of visible symptoms (e.g., Gravano et al 2004;Innes et al 1996Innes et al , 2001Novak et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…However, the leaves that were used for photosynthesis and fluorescence measurements in our study had little symptomatic dots, since they were chosen from the middle of the canopy, and it has been shown that during the early stages of the ozone injury photosynthetic efficiency may also be stimulated owing to the activation of metabolic responses to compensate for the reduced number of photosynthetically active cells (Gravano et al 2004).…”
Section: Ozone Damage Of Birches Emerges With Timementioning
confidence: 99%